PERENCANAAN EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS HIGER ORDER THINKING SKILLS (HOTS) MENINGKATKAN KEMAMPUAN BERFIKIR KRITIS PESERTA DIDIK - Luna Aiswara; Sikha Nur Inayah; Agus Nur Kholis; Hafidz Al Faqih; Ma’mun Hanif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the concept, planning, implementation, and contribution of Higher Order Thinking Skills (HOTS)-based assessment in Islamic Religious Education (IRE) learning to improve students' critical thinking skills. This research employed a qualitative approach using a library research method. Data were collected through the review of various relevant literature sources, including books, scientific journals, articles, and previous research findings, and were analyzed using content analysis techniques. The results indicate that HOTS-based assessment planning in IRE learning is conducted systematically through determining assessment objectives, formulating indicators, developing test blueprints, constructing assessment instruments, and selecting appropriate assessment techniques. HOTS-based assessment focuses on students' abilities to analyze (C4), evaluate (C5), and create (C6) according to the revised Bloom’s Taxonomy. The implementation of HOTS-based assessment in IRE learning can be carried out through various strategies, such as Problem-Based Learning, Project-Based Learning, and Inquiry Learning, which encourage students to think critically, creatively, and solve problems based on Islamic values. Therefore, HOTS-based assessment contributes significantly to the development of students' critical, reflective, and creative thinking skills, enabling them to face life challenges more wisely and contextually.